2012
DOI: 10.5897/ajar11.1302
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of loan repayment capacity of small-holder cooperative farmers in Yewa North Local Government Area of Ogun State, Nigeria

Abstract: Farm credits played vital roles in the socioeconomic transformation of the rural economies. However, their acquisition and repayment were characterized by numerous challenges including high levels of default among beneficiaries. This study analyzed the smallholder farmers' loan repayment capacity using household data from 110 cooperative farmers from selected villages in Ogun State, Nigeria. Specifically, the socioeconomic and demographic characteristics of respondents, loan repayment rate and factors influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Others have focused on the characteristics of the lending institutions and the type of loans such as their size, whether the loan was approved for income generating activities, etc. (Gebeyehu, Beshire, & Haji, 2013;Ojiako & Ogbukwa, 2012;Tedeschi, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Others have focused on the characteristics of the lending institutions and the type of loans such as their size, whether the loan was approved for income generating activities, etc. (Gebeyehu, Beshire, & Haji, 2013;Ojiako & Ogbukwa, 2012;Tedeschi, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Their findings indicated a positive correlation between loan repayment perception and cohesion, leading to a recommendation that extension agents leverage the effect of cohesion on loan repayment to promote it in upcoming cooperative societies. Another study conducted by Ojiako and Ogbukwa [26] found that farm credits play a significant role in the socio-economic transformation of rural economies. The findings showed that cooperative membership was positively linked to farm performance, and the study recommended further government and NGO interventions to encourage individual farmers to join cooperatives and operate within organised groups.…”
Section: Empirical Studies Of the Role Of Agricultural Cooperatives I...mentioning
confidence: 99%
“…The most recent related study by Ifeanyi and Ogbukwa (2012) also uses the socio-economic and demographic characteristics of respondents to examined credit repayment rate and factors influencing repayment capacity of small holder farmers in Nigeria. Aside using purposive selection multistage random sampling technique in selecting the sample, their data were analyzed using descriptive statistics, correlation and regression techniques.…”
Section: Empirical Studies Of Determinants Of Default Ratesmentioning
confidence: 99%